Preoperative Determination of Tibia Length Using Contralateral Tibial Tubercle-Medial Malleolar Distance (TMD) in Western Part of Nepal - Shrestha, Kishor Man; Kandel, Prakriti Raj; Shrestha, Bipan; Shrestha, Shreshal (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION Intramedullary (IM) nailing is most commonly preferred for adult tibial shaft fracture. The objective of this study was to find the accuracy of predicting the tibial nail length pre-operatively from contra-lateral tibial tubeorsity to medial malleolar distance (TMD) length. MATERIAL AND METHODS After ethical clearance (UCMS/IRC/239/19) from the Institutional Review Board (IRB) of Universal College of Medical Sciences, all patients with recent fracture of tibia, who fulfilled the inclusion criteria were enrolled in the study and the informed written consent was obtained. The study was conducted on 45 patients of aged more than 15 years who attended Universal College of Medical Sciences Teaching Hospital (UCMS-TH) over a period of one year (Nov 2019 to Oct 2020). The TMD length of contra-lateral leg were measured preoperatively using a measuring tape and the ideal length of IM nail were measured intra-operatively using IM tibial nail under fluoroscopic guidance. RESULTS Analysis showed that majority of patients were males (77.78%) out of total 45 patients. The mean length of TMD length of contra-lateral leg and the ideal length of IM nail were 33.067 ±1.60 and 33.11 ±1.68 respectively. The mean difference between these two measurements was 0.04 (95% CI, -0.64 to 0.72). The significant correlation was found between these two measurements i.e r=0.88 by Pearson’s correlation (95% CI, 0.79 to 0.93), (p<0.001). Most of the TMD length were equal (37.78%) to ideal length of IM nail. CONCLUSION We recommended TMD length measurement of contralateral leg as an excellent anthropometric parameter for preoperative planning.